Rigid element model for in-plane dynamics of masonry walls considering hysteretic behaviour and damage. - Casolo, Siro
A specific rigid element approach is proposed for the in-plane dynamical analysis of masonry walls, whose seismic performance is strongly related to mechanical deterioration and hysteretic energy dissipation. Since the execution of effective time-history analysis necessitates the use of discrete models with reduced number of degrees of freedom, the tricky issue lies in achieving a balance between accuracy in the geometrical description and the need for a realistic damage material model. For this reason, a mechanistic ?rigid body spring model? (RBSM) was adopted, which consists of a collection of plane quadrilateral rigid elements connected to each other by two normal springs and one shear spring at each side. The material model was based on a phenomenological description of the cyclic response of masonry, and specific separate hysteretic laws were assigned for the axial and shear deformation between the elements. This separation led to a large reduction in computational effort, though a Coulomb-like law was adopted in order to relate the strength of the shear springs to the vertical axial loading. The effective performance of the present approach is demonstrated by the numerical validation and by comparisons with some well-known experimental and numerical tests presented in the literature.
Keywords: Degradation; Dynamics; Hysteretic material; In-plane.; Masonry; Rigid elements